The Effect of Water Temperature on Incubation Period, Hatching Rate, Normalities of The Larvae and Survival Rate of Snakehead Fish Channa striata - Muslim, Muslim; Fitrani, Mirna; Afrianto, A.M. (Aquacultura Indonesiana, 2018)
The aims of this research were to determine the hatching performance of snakehead fish egg which incubated at different water temperature. This research had been conducted in the Fish Breeding Unit “Batanghari Sembilan”, Indralaya South Sumatera Indonesia. This research was an experimental research with 5 treatments of water temperature P1 (26 ± 0.5°C), P2 (28 ± 0.5°C), P3 (30 ± 0.5°C), P4 (32 ± 0.5°C), P5 (34 ± 0.5°C) and 3 repetitions. The results showed that incubation period needed at P1: 30.01 hours, P2: 28.02 hours, P3:23.13 hours, P4: 21.03 hours, P5: 20.12 hours. The best treatment for hatching rate, normality and survival rate were P2 treatment, 86.33%, 100% and 97.3%, respectively.  Even though the fastest incubation period was the P5 treatment (20.12 hours). Water quality of the research was intolerance range, pH (4.17-5.32) and Dissolved Oxygen (6.23-6.71 mg.L-1). Based on the results acquired, incubation temperature at 28 ± 0.5°C produced the best hatching rate, normality, and survival rate.